Liquid crystal polyester as well as preparation method and application thereof

The liquid crystal polyester prepared by polymerizing specific chemical substances solves the problem that traditional liquid crystal polyester is difficult to have low dielectric constant and low dielectric loss at high frequencies, realizes application requirements in the field of high-frequency communications, and improves heat resistance and solubility.

CN119751837AActive Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411882604.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Traditional liquid crystal polyester is difficult to have low dielectric constant and low dielectric loss at high frequencies, and is insufficient in heat resistance and solubility, making it difficult to meet the application requirements in the field of 5G communications.

Method used

By polymerizing alicyclic imide diacid, aromatic diacid, hydroxy aromatic carboxylic acid and aromatic diphenol, a new liquid crystal polyester is prepared, which has low dielectric constant and low dielectric loss at high frequency, and has high glass transition temperature and good solubility.

Benefits of technology

It realizes the combination of low dielectric constant and low dielectric loss at high frequency, improves heat resistance and solubility, and is suitable for industrial applications as electronic circuit substrates in the field of 5G communications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751837A_ABST
    Figure CN119751837A_ABST
Patent Text Reader

Abstract

The invention discloses liquid crystal polyester as well as a preparation method and application thereof. The liquid crystal polyester is formed by polymerizing alicyclic imide diacid, aromatic diacid, hydroxyl aromatic carboxylic acid and aromatic diphenol. The preparation method of the liquid crystal polyester comprises the following steps: mixing alicyclic imide-containing diacid, aromatic diacid and hydroxyl aromatic carboxylic acid for polymerization reaction, and then adding aromatic diphenol for polymerization reaction to obtain the liquid crystal polyester. The liquid crystal polyester has the advantages of low dielectric constant at high frequency, low dielectric loss at high frequency, good heat resistance, good solubility and the like, the preparation method is simple, and the liquid crystal polyester is suitable for large-scale industrial application in the field of 5G communication as an electronic circuit substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a liquid crystal polyester and a preparation method and application thereof. Background Art

[0002] With the development of 5G communications, the frequency of signal processing and transmission of electronic devices has been greatly improved, and low dielectric constant (D k ) and low dielectric loss (D f ) performance requirements. Liquid crystal polyester (LCP) refers to a polyester resin that can form a liquid crystal state under certain conditions. It has excellent dielectric properties, low hygroscopicity, high dimensional stability and other properties. LCP film has a very broad application prospect in the field of flexible copper clad laminate (FCCL).

[0003] However, the glass transition temperature (T g ) is generally low (usually below 150°C), so the heat resistance is poor. Moreover, the solubility of traditional liquid crystal polyesters is generally poor, and they need to be dissolved in highly corrosive solvents, which are difficult to handle or operate, and chlorine-containing solvents are prone to residual chloride ions, which will corrode circuits. In addition, although traditional liquid crystal polyesters have low dielectric loss at high frequencies (≥10GHz), their dielectric constants are large. The commonly used means of reducing the dielectric constant (for example, introducing fluorine atoms, large side groups, etc.) can reduce the dielectric constant of liquid crystal polyesters to a certain extent, but at the same time, it will also destroy the liquid crystallinity of liquid crystal polyesters, causing the dielectric loss of liquid crystal polyesters at high frequencies to increase, and ultimately making it difficult for liquid crystal polyesters to have both low dielectric constants and low dielectric losses at high frequencies. In summary, traditional liquid crystal polyesters still have obvious defects and are still difficult to meet the growing requirements of practical applications.

[0004] Therefore, it is of great significance to develop a liquid crystal polyester that has both low dielectric constant and low dielectric loss, good heat resistance and good solubility at high frequencies. Summary of the invention

[0005] The purpose of the present invention is to provide a liquid crystal polyester and a preparation method and application thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A liquid crystal polyester is prepared by polymerizing alicyclic imide diacid, aromatic diacid, hydroxy aromatic carboxylic acid and aromatic diphenol.

[0008] Preferably, the molar ratio of the carboxyl group to the hydroxyl group in the alicyclic imide diacid, aromatic diacid, hydroxy aromatic carboxylic acid and aromatic diphenol is 1:0.7-1.3.

[0009] More preferably, the molar ratio of the carboxyl group to the hydroxyl group in the alicyclic imide diacid, aromatic diacid, hydroxy aromatic carboxylic acid and aromatic diphenol is 1:0.95-1.05.

[0010] Preferably, the content of repeating units derived from alicyclic imide diacids in the liquid crystal polyester is 1 mol% to 29 mol%, the content of repeating units derived from aromatic diacids is 1 mol% to 29 mol%, the content of repeating units derived from hydroxyaromatic carboxylic acids is 30 mol% to 70 mol%, and the content of repeating units derived from aromatic diphenols is 1 mol% to 29 mol%.

[0011] Further preferably, the content of repeating units derived from alicyclic imide diacids in the liquid crystal polyester is 5 mol% to 20 mol%, the content of repeating units derived from aromatic diacids is 5 mol% to 15 mol%, the content of repeating units derived from hydroxyaromatic carboxylic acids is 40 mol% to 60 mol%, and the content of repeating units derived from aromatic diphenols is 20 mol% to 29 mol%.

[0012] Preferably, the structural formula of the alicyclic imide diacid is:

[0013] In the formula, X is one of cyclobutyl, cyclopentyl and cyclohexyl, R1 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl, R2 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl, R3 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl, and R4 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl.

[0014] Preferably, X is one of cyclobutyl and cyclohexyl.

[0015] Preferably, R1 is hydrogen or methyl.

[0016] Preferably, R2 is hydrogen or methyl.

[0017] Preferably, R3 is hydrogen or methyl.

[0018] Preferably, R4 is hydrogen or methyl.

[0019] Preferably, the aromatic diacid is at least one of terephthalic acid, isophthalic acid, 2,3,5,6-tetrafluoroterephthalic acid, 2,6-naphthalene dicarboxylic acid, and 4,4'-diphenyl ether dicarboxylic acid.

[0020] More preferably, the aromatic diacid is at least one of terephthalic acid, isophthalic acid, and 4,4'-diphenyl ether dicarboxylic acid.

[0021] Preferably, the hydroxyaromatic carboxylic acid is at least one of 4-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 1-hydroxy-4-naphthoic acid and 4-hydroxy-6-naphthoic acid.

[0022] More preferably, the hydroxyaromatic carboxylic acid is at least one of 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid.

[0023] Preferably, the aromatic diphenol is at least one of hydroquinone, resorcinol, methylhydroquinone, 2-methoxyhydroquinone, 2-phenylhydroquinone, bisphenol A, bisphenol AF, tetrafluorohydroquinone, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenylmethane, 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, and 2,7-dihydroxynaphthalene.

[0024] More preferably, the aromatic diphenol is at least one of 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether and 4,4'-dihydroxydiphenylmethane.

[0025] Preferably, the weight average molecular weight of the liquid crystal polyester is 10,000-150,000.

[0026] More preferably, the weight average molecular weight of the liquid crystal polyester is 20,000-100,000.

[0027] A method for preparing the liquid crystal polyester as described above comprises the following steps: mixing alicyclic imide diacid, aromatic diacid and hydroxy aromatic carboxylic acid for polymerization reaction, and then adding aromatic diphenol for polymerization reaction to obtain liquid crystal polyester.

[0028] Preferably, the polymerization reaction is one of melt polymerization, solution polymerization, slurry polymerization and solid phase polymerization.

[0029] A film comprising the above liquid crystal polyester.

[0030] An application of the liquid crystal polyester as described above as an electronic circuit substrate in the field of 5G communications.

[0031] The beneficial effects of the present invention are: the liquid crystal polyester of the present invention has the advantages of low dielectric constant at high frequency, low dielectric loss at high frequency, good heat resistance, good solubility, etc., and its preparation method is simple, and it is suitable for large-scale industrial application as an electronic circuit substrate in the 5G communication field.

[0032] Specifically:

[0033] 1) The liquid crystal polyester of the present invention has both low dielectric constant and low dielectric loss at high frequencies, and is suitable for use as a high-frequency communication substrate, and has a very broad application prospect;

[0034] 2) The liquid crystal polyester of the present invention has a high glass transition temperature, good heat resistance and a wide range of applications;

[0035] 3) The liquid crystal polyester of the present invention contains alicyclic imide structural units, which can effectively improve the solubility of the liquid crystal polyester, so that the liquid crystal polyester has good solubility in conventional organic solvents, and is convenient for solution processing to prepare LCP films;

[0036] 4) The preparation method of the liquid crystal polyester of the present invention is simple and suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the liquid crystal polyester in Example 1 1 H NMR spectra.

[0038] Figure 2 FT-IR graphs of the liquid crystal polyesters in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0039] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0040] Embodiment 1:

[0041] A liquid crystal polyester, the preparation method of which is as follows:

[0042] Under nitrogen protection, 3.8 mL (30.0 mmol) of benzenesulfonyl chloride (BsCl), 2.3 mL (30.0 mmol) of N,N-dimethylformamide (DMF) and 10 mL of pyridine (Py) were added to a three-necked flask, and the mixture was left to stand at room temperature for 30 min for activation. Then, stirring was started, and 0.50 g (3.0 mmol) of isophthalic acid (IPA) and 0.98 g (2.0 mmol) of alicyclic imide diacid (M w=490.14), stirred at room temperature for 10 min, then transferred the three-necked flask to an oil bath at 120°C and stirred for 10 min, then 1.38 g (10 mmol) of 4-hydroxybenzoic acid (HBA) was dissolved in 10 mL of Py and quickly added to the three-necked flask, stirred at 120°C for 30 min, then 0.47 g (2.5 mmol) of 4,4'-dihydroxybiphenyl (BP) and 0.50 g (2.5 mmol) of 4, 4'-Dihydroxydiphenylmethane (DPM) was dissolved in 10 mL of Py, and then added dropwise to a three-necked flask using a constant pressure dropping funnel for 30 minutes. After the addition was completed, the mixture was stirred and reacted at 120°C for 3 hours, cooled to room temperature, and the obtained polymer solution (viscous) was added dropwise to ethanol for precipitation. The solid product (off-white, fibrous) was washed several times with an appropriate amount of ethanol and then filtered, and then placed in an oven at 110°C for 24 hours to obtain a liquid crystal polyester (weight average molecular weight of 35200).

[0043] Note:

[0044] The structural formula of the alicyclic imide diacid used in this embodiment is as follows:

[0045]

[0046] A film, the preparation method of which is as follows:

[0047] Add 0.4 g of the above liquid crystal polyester to 20 mL of N-methyl-2-pyrrolidone (NMP), heat to 140°C, stir to obtain a uniform transparent solution, filter, apply the filtrate on a clean glass plate, let it stand, then put it in an oven, bake at 100°C for 6 hours, bake at 210°C for 1 hour, cool to room temperature, and soak in water for 2 hours. Then peel off the film formed on the glass plate, and then put it in an oven and bake at 110°C for 12 hours to obtain a film.

[0048] Embodiment 2:

[0049] A liquid crystal polyester, the preparation method of which is as follows:

[0050] Under nitrogen protection, 3.8 mL (30.0 mmol) of benzenesulfonyl chloride (BsCl), 2.3 mL (30.0 mmol) of N,N-dimethylformamide (DMF) and 10 mL of pyridine (Py) were added to a three-necked flask, and the mixture was left to stand at room temperature for activation for 30 min. Then, stirring was started, and 0.50 g (3.0 mmol) of isophthalic acid (IPA) and 0.98 g (2.0 mmol) of alicyclic imide diacid (same as in Example 1) were added. The mixture was stirred at room temperature for 10 min. The three-necked flask was then transferred to an oil bath at 120° C. and stirred for 10 min. Then, 1.38 g (10 mmol) of 4-hydroxybenzoic acid (HBA) was added with 10 mL of Py. Dissolve, then quickly add to a three-necked flask, stir and react at 120°C for 30 minutes, then dissolve 0.47g (2.5mmol) of 4,4'-dihydroxybiphenyl (BP) and 0.51g (2.5mmol) of 4,4'-dihydroxydiphenyl ether (ODP) in 10mL of Py, and then add dropwise to the three-necked flask with a constant pressure dropping funnel for 30 minutes. After the addition is completed, stir and react at 120°C for 3 hours, cool to room temperature, and then add the obtained polymer solution (viscous) dropwise to ethanol for precipitation. Take the solid product (offwhite, fibrous), wash it with an appropriate amount of ethanol several times, filter it, and then place it in an oven at 110°C for 24 hours to obtain a liquid crystal polyester (weight average molecular weight of 40500).

[0051] A film, the preparation method of which is as follows:

[0052] Add 0.4 g of the above liquid crystal polyester to 20 mL of N-methyl-2-pyrrolidone (NMP), heat to 140°C, stir to obtain a uniform transparent solution, filter, apply the filtrate on a clean glass plate, let it stand, then put it in an oven, bake at 100°C for 6 hours, bake at 210°C for 1 hour, cool to room temperature, and soak in water for 2 hours. Then peel off the film formed on the glass plate, and then put it in an oven and bake at 110°C for 24 hours to obtain a thin film.

[0053] Embodiment 3:

[0054] A liquid crystal polyester, the preparation method of which is as follows:

[0055] Under nitrogen protection, 3.8 mL (30.0 mmol) of benzenesulfonyl chloride (BsCl), 2.3 mL (30.0 mmol) of N,N-dimethylformamide (DMF) and 10 mL of pyridine (Py) were added to a three-necked flask, and the mixture was left to stand at room temperature for 30 min for activation. Then, stirring was started, and 0.50 g (3.0 mmol) of isophthalic acid (IPA) and 0.98 g (2.0 mmol) of alicyclic imide diacid (M w=462.11), stirred at room temperature for 10 min, then transferred the three-necked flask to an oil bath at 120°C and stirred for 10 min, then 1.38 g (10 mmol) of 4-hydroxybenzoic acid (HBA) was dissolved in 10 mL of Py and quickly added to the three-necked flask, stirred at 120°C for 30 min, then 0.47 g (2.5 mmol) of 4,4'-dihydroxybiphenyl (BP) and 0.50 g (2.5 mmol) of 4, 4'-Dihydroxydiphenylmethane (DPM) was dissolved in 10 mL of Py, and then added dropwise to a three-necked flask using a constant pressure dropping funnel for 30 minutes. After the addition was completed, the mixture was stirred and reacted at 120°C for 3 hours, cooled to room temperature, and the obtained polymer solution (viscous) was added dropwise to ethanol for precipitation. The solid product (off-white, fibrous) was washed several times with an appropriate amount of ethanol and then filtered, and then placed in an oven at 110°C for 24 hours to obtain a liquid crystal polyester (weight average molecular weight of 28600).

[0056] Note:

[0057] The structural formula of the alicyclic imide diacid used in this embodiment is as follows:

[0058]

[0059] A film, the preparation method of which is as follows:

[0060] Add 0.4 g of the above liquid crystal polyester to 20 mL of N-methyl-2-pyrrolidone (NMP), heat to 140°C, stir to obtain a uniform transparent solution, filter, apply the filtrate on a clean glass plate, let it stand, then put it in an oven, bake at 100°C for 6 hours, bake at 210°C for 1 hour, cool to room temperature, and soak in water for 2 hours. Then peel off the film formed on the glass plate, and then put it in an oven and bake at 110°C for 24 hours to obtain a thin film.

[0061] Embodiment 4:

[0062] A liquid crystal polyester, the preparation method of which is as follows:

[0063] Under nitrogen protection, 3.8 mL (30.0 mmol) of benzenesulfonyl chloride (BsCl), 2.3 mL (30.0 mmol) of N,N-dimethylformamide (DMF) and 10 mL of pyridine (Py) were added to a three-necked flask, and the mixture was left to stand at room temperature for activation for 30 min. Then, stirring was started, and 0.50 g (3.0 mmol) of isophthalic acid (IPA) and 0.98 g (2.0 mmol) of alicyclic imide diacid (same as in Example 3) were added. The mixture was stirred at room temperature for 10 min, and the three-necked flask was transferred to an oil bath at 120° C. and stirred for 10 min. Then, 1.38 g (10 mmol) of 4-hydroxybenzoic acid (HBA) was added with 10 mL of Py. Dissolve, then quickly add to a three-necked flask, stir and react at 120°C for 30 minutes, then dissolve 0.47g (2.5mmol) of 4,4'-dihydroxybiphenyl (BP) and 0.51g (2.5mmol) of 4,4'-dihydroxydiphenyl ether (ODP) in 10mL of Py, and then add dropwise to the three-necked flask with a constant pressure dropping funnel for 30 minutes. After the addition is completed, stir and react at 120°C for 3 hours, cool to room temperature, and then add the obtained polymer solution (viscous) dropwise to ethanol for precipitation. Take the solid product (offwhite, fibrous), wash it with an appropriate amount of ethanol several times, filter it, and then place it in an oven at 110°C for 24 hours to obtain a liquid crystal polyester (weight average molecular weight of 24300).

[0064] A film, the preparation method of which is as follows:

[0065] Add 0.4 g of the above liquid crystal polyester to 20 mL of N-methyl-2-pyrrolidone (NMP), heat to 140°C, stir to obtain a uniform transparent solution, filter, apply the filtrate on a clean glass plate, let it stand, then put it in an oven, bake at 100°C for 6 hours, bake at 210°C for 1 hour, cool to room temperature, and soak in water for 2 hours. Then peel off the film formed on the glass plate, and then put it in an oven and bake at 110°C for 24 hours to obtain a thin film.

[0066] Comparative Example 1: (without using imide diacid)

[0067] A liquid crystal polyester, the preparation method of which is as follows:

[0068] Under nitrogen protection, 3.8 mL (30.0 mmol) of benzenesulfonyl chloride (BsCl), 2.3 mL (30.0 mmol) of N,N-dimethylformamide (DMF) and 10 mL of pyridine (Py) were added to a three-necked flask, and the mixture was left to stand at room temperature for 30 min for activation. Then, stirring was started, and 0.83 g (5.0 mmol) of isophthalic acid (IPA) was added. The mixture was stirred at room temperature for 10 min. The three-necked flask was then transferred to an oil bath at 120 °C and stirred for 10 min. Then, 1.38 g (10 mmol) of 4-hydroxybenzoic acid (HBA) was dissolved in 10 mL of Py and quickly added to the three-necked flask. In a flask, stir and react at 120°C for 30 minutes, then dissolve 0.47g (2.5mmol) of 4,4'-dihydroxybiphenyl (BP) and 0.50g (2.5mmol) of 4,4'-dihydroxydiphenylmethane (DPM) in 10mL of Py, and then add dropwise to the three-necked flask using a constant pressure dropping funnel for 30 minutes. After the addition is completed, stir and react at 120°C for 3 hours, cool to room temperature, and then add the obtained polymer solution (viscous) dropwise to ethanol for precipitation. Take the solid product (off-white, fibrous), wash it with an appropriate amount of ethanol for several times, filter it, and then place it in an oven at 110°C for 24 hours to obtain a liquid crystal polyester.

[0069] Comparative Example 2: (the imide diacid used does not contain an alicyclic structure)

[0070] A liquid crystal polyester, the preparation method of which is as follows:

[0071] Under nitrogen protection, 3.8 mL (30.0 mmol) of benzenesulfonyl chloride (BsCl), 2.3 mL (30.0 mmol) of N,N-dimethylformamide (DMF) and 10 mL of pyridine (Py) were added to a three-necked flask, and the mixture was left to stand at room temperature for 30 min for activation. Then, stirring was started, and 0.58 g (3.5 mmol) of isophthalic acid (IPA) and 1.02 g (1.5 mmol) of imide diacid (M w=678.2), stirred at room temperature for 10 min, then transferred the three-necked flask to an oil bath at 120°C and stirred for 10 min, then 1.38 g (10 mmol) of 4-hydroxybenzoic acid (HBA) was dissolved in 10 mL of Py and quickly added to the three-necked flask, stirred at 120°C for 30 min, then 0.47 g (2.5 mmol) of 4,4'-dihydroxybiphenyl (BP) and 0.51 g (2.5 mmol) of 4, 4'-Dihydroxydiphenyl ether (ODP) was dissolved in 10 mL of Py, and then added dropwise to a three-necked flask using a constant pressure dropping funnel for 15 minutes. After the addition was completed, the reaction was stirred at 120°C for 4 hours, cooled to room temperature, and the obtained polymer solution (viscous) was added dropwise to ethanol for precipitation. The solid product (off-white, fibrous) was washed with an appropriate amount of ethanol for several times and then filtered, and then placed in an oven at 110°C for 24 hours to obtain a liquid crystal polyester (weight average molecular weight of 25000).

[0072] Note:

[0073] The structural formula of the imide diacid used in this comparative example is as follows:

[0074]

[0075] A film, the preparation method of which is as follows:

[0076] Add 0.4 g of the above liquid crystal polyester to 20 mL of N-methyl-2-pyrrolidone (NMP), heat to 140°C, stir to obtain a uniform transparent solution, filter, apply the filtrate on a clean glass plate, let it stand, then put it in an oven, bake at 100°C for 6 hours, bake at 210°C for 1 hour, cool to room temperature, and soak in water for 2 hours. Then peel off the film formed on the glass plate, and then put it in an oven and bake at 110°C for 24 hours to obtain a thin film.

[0077] Performance Test:

[0078] 1) H NMR spectrum of the liquid crystal polyester in Example 1 ( 1 H NMR) Figure 1 shown.

[0079] Depend on Figure 1It can be seen that: from low field to high field, the spectrum peaks between 9.08ppm and 7.04ppm belong to the aromatic hydrogen protons on the benzene rings in the monomer units containing alicyclic imide diacid, isophthalic acid, 4-hydroxybenzoic acid, 4,4'-dihydroxybiphenyl and 4,4'-dihydroxydiphenylmethane, 4.00ppm is the absorption peak of hydrogen on the methylene between the benzene rings in the 4,4'-dihydroxydiphenylmethane monomer unit, 3.50ppm to 2.20ppm are the peaks of methyl and alicyclic structure hydrogen atoms on the monomer units containing alicyclic imide diacid, and there is no proton signal peak of hydroxyl at around 9.45ppm. In summary, this embodiment prepares a liquid crystal polyester with the expected structure.

[0080] 2) The infrared spectra (FT-IR) of the liquid crystal polyester in Example 1 and Comparative Example 1 are as follows: Figure 2 shown.

[0081] Depend on Figure 2 It can be seen that the liquid crystal polyester in Example 1 has a -1 ~2920cm -1 The absorption peaks at 1730 cm-1 and 1740 cm-2, which are attributed to the methyl and methylene groups in the alicyclic imide diacid monomer structure, appeared. -1 The absorption peak attributable to the stretching vibration of the carbonyl C=O of the ester appears at 1370 cm -1 and 720cm -1 The stretching vibration peaks attributable to the CN bond of the imide ring and the bending vibration peaks of the imide ring appeared at 3600 cm-1 and 3600 cm-2, respectively. The appearance of these peaks indicates that the alicyclic imide diacid structure has been successfully introduced into the molecular chain of the liquid crystal polyester. -1 ~3500cm -1 The intensity of the broad peak attributable to the hydroxyl group is greatly reduced, indicating that the hydroxyl and carboxyl groups in the monomer have been basically reacted completely. At the same time, the spectrum does not contain any structural signals related to polyimide, indicating that the liquid crystal polyester in Comparative Example 1 is just an ordinary polyester polymer.

[0082] 3) The performance test results of the liquid crystal polyester / film in Examples 1 to 4 and Comparative Examples 1 to 2 are shown in the following table:

[0083] Table 1 Performance test results of liquid crystal polyester / film

[0084]

[0085] Note:

[0086] Glass transition temperature (T g ): In N2 atmosphere, the T of the liquid crystal polyester sample was measured by differential scanning calorimetry. gThe test temperature range is 0℃~370℃, the first heating rate is 30℃ / min, the cooling rate is 10℃ / min, the second heating rate is 30℃ / min, T g Taken from the second heating curve.

[0087] Solubility: Take 10 mg of liquid crystal polyester sample and dissolve it in 1 mL of solvent. Let it stand at room temperature for one day and observe the dissolution of the sample. If it is difficult to dissolve, heat it to the boiling point of the solvent and then observe the change in solubility. "++" means soluble at room temperature, "+" means soluble by heating, and "-" means insoluble.

[0088] Dielectric constant (D k ) and dielectric loss factor (D f ): A high-frequency network tester (PNA-L NetworkAnalyzer N5234B) was used for testing. The size of the film sample was 6cm×6cm and the test was performed at 10GHz.

[0089] Tensile strength and tensile modulus: According to the 5967 tensile mode of ASTM D882-12 material testing system, the film samples were cut into dumbbell-shaped standard tensile specimens with a size of 120mm×15mm. The test was carried out at room temperature with a tensile load of 1000N and a specimen tensile rate of 5mm / min. Each specimen was tested 5 times in parallel and the average value was taken.

[0090] From Table 1, we can see that:

[0091] a) The liquid crystal polyesters in Examples 1 to 4 have lower dielectric constants and dielectric losses at high frequencies and also have higher T g and excellent mechanical properties;

[0092] b) The solubility of the liquid crystal polyester in Comparative Example 1 is very poor, significantly inferior to that of the liquid crystal polyesters in Examples 1 to 4, indicating that the introduction of alicyclic imide structural units can effectively improve the solubility of the liquid crystal polyester;

[0093] c) The liquid crystal polyester in Comparative Example 2 is a polyester-type liquid crystal in which phenyl groups are introduced as large side groups. It and the liquid crystal polyesters in Examples 1 to 4 have good solubility and high thermodynamic properties, but the liquid crystal polyesters in Examples 1 to 4 have significantly lower dielectric constants and dielectric losses at high frequencies (for example, the dielectric constant of the liquid crystal polyester in Example 3 is reduced by 7.8%, and the dielectric loss is reduced by 36.4% compared with the liquid crystal polyester in Comparative Example 2), indicating that the liquid crystal polyesters in Examples 1 to 4 have greater potential for application as substrates in the field of high-frequency communications;

[0094] In summary, the liquid crystal polyester in the present invention has excellent solubility and heat resistance, and also has a lower dielectric constant and dielectric loss at high frequencies, and can be used in the fields of insulation, high-frequency flexible copper clad laminates, etc.

[0095] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A liquid crystal polyester, characterized in that: It is prepared by polymerization of alicyclic imide diacid, aromatic diacid, hydroxy aromatic carboxylic acid and aromatic diphenol.

2. The liquid crystal polyester according to claim 1, characterized in that: The liquid crystal polyester contains 1 mol% to 29 mol% of repeating units derived from alicyclic imide diacids, 1 mol% to 29 mol% of repeating units derived from aromatic diacids, 30 mol% to 70 mol% of repeating units derived from hydroxyaromatic carboxylic acids, and 1 mol% to 29 mol% of repeating units derived from aromatic diphenols.

3. The liquid crystal polyester according to claim 1 or 2, characterized in that: The structural formula of the alicyclic imide diacid is: In the formula, X is one of cyclobutyl, cyclopentyl and cyclohexyl, R1 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl, R2 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl, R3 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl, and R4 is one of hydrogen, C1-C4 alkyl, methoxy and trifluoromethyl.

4. The liquid crystal polyester according to claim 1 or 2, characterized in that: The aromatic diacid is at least one of terephthalic acid, isophthalic acid, 2,3,5,6-tetrafluoroterephthalic acid, 2,6-naphthalene dicarboxylic acid, and 4,4'-diphenyl ether dicarboxylic acid.

5. The liquid crystal polyester according to claim 1 or 2, characterized in that: The hydroxy aromatic carboxylic acid is at least one of 4-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 1-hydroxy-4-naphthoic acid and 4-hydroxy-6-naphthoic acid.

6. The liquid crystal polyester according to claim 1 or 2, characterized in that: The aromatic diphenol is at least one of hydroquinone, resorcinol, methyl hydroquinone, 2-methoxyhydroquinone, 2-phenylhydroquinone, bisphenol A, bisphenol AF, tetrafluorohydroquinone, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenylmethane, 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, and 2,7-dihydroxynaphthalene.

7. The liquid crystal polyester according to claim 1 or 2, characterized in that: The weight average molecular weight of the liquid crystal polyester is 10,000 to 150,000.

8. A method for preparing a liquid crystal polyester as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing alicyclic imide diacid, aromatic diacid and hydroxy aromatic carboxylic acid for polymerization reaction, and then adding aromatic diphenol for polymerization reaction to obtain liquid crystal polyester.

9. A film, characterized in that: The invention comprises the liquid crystal polyester according to any one of claims 1 to 7.

10. An application of the liquid crystal polyester as described in any one of claims 1 to 7 as an electronic circuit substrate in the field of 5G communications.

Citation Information

Patent Citations

  • Aromatic polyesterimide and preparation method thereof

    CN106810695A

  • Thermotropic liquid crystal polyester compound and preparation method thereof

    CN117986553A

  • Process for direct polycondensation synthesis of thermotropic high molecule liquid crystal polyester imide

    CN1385456A